COMPARATIVE ANALYSIS OF THE RESULTSOF AN EXPERIMENTAL STUDY WITH BASIC EQUIPMENT AND A SPECIALLY MADE ONE TOTHE INSIZE ISR - C002 ROUGHNESS TESTER (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The present research presents a comparative analysis between experiments conducted with basic equipment for a portable INSIZE ISR - C002 roughness tester and a specially made for the purpose attachment to the device. An analysis is made of the proposed basic device for working with a portable roughness tester INSIZE ISR - C002, and its shortcomings have been determined. In order to facilitate the operator's work with the device and obtain more accurate results, a special device is developed. It is designed using CAD/CAM products and manufactured using additive printing (3D printing). The additive printing technology used reduces its cost. The manufactured device is analyzed and its advantages and disadvantages are determined. Experiments are conducted with both devices and a comparative analysis of the obtained results is made. An analysis of the measurement system (MSA) is made, through which the results of the conducted experiments were analyzed. The comparative analysis shows a number of advantages of the new device compared to the basic one, which provide a basis for the formulated conclusions and recommendations.